Social Support and Sexual Risk Among Establishment-Based Female Sex Workers in Tijuana. - Choudhury, Shonali Mona; Erausquin, Jennifer Toller; Park, Kyuwon; Anglade, Debbie (Qualitative health research, 2015)
Social support can affect health outcomes of female sex workers. In this inductive feminist grounded theory study based on 20 in-depth interviews, we explore how establishment-based female sex workers in Tijuana perceive the impact of the connections among women on their lives and health. Participants elected to discuss the importance of social support from mothers, sisters, friends, and co-workers, and the empowering and disempowering aspects of these relationships. In previous studies, scholars demonstrated the efficacy of formal organization of female sex workers in promoting the mitigation of sexual and HIV risk. We show the importance of informal ties with other women. Some participants mentioned competitive relationships, others talked about cooperation and the desire for a venue to learn from one another. Social interactions with other women are especially empowering when female sex workers can openly engage in "woman talk" that may contribute to the mitigation of sexual and HIV risk.